Development of alternative and viable culture media for the microbial growth of Bacillus Subtilis: Development of alternative and viable culture media for the microbial growth of Bacillus Subtilis (La U Investiga, 2021)
Culture media are made up of: a carbon source is usually simple sugars such as glucose or lactose. The objective of this research was to develop alternative and viable culture media for the microbial growth of Bacillus subtilis, useful in laboratory practices. It was started from the description of the main culture media used within the laboratory, household inputs such as panela, sugar, low-cost honey were identified to replace commercial inputs. The experimental design was carried out with the variables of carbon sources and brix degrees, maintaining a similar structure to commercial culture media. Once its elaboration was executed, the viability of the culture media was determined, using a bacterium under controlled conditions within the laboratory, through the inoculation of Bacillus subtilis in a dilution of 105, incubating at 25 ° C for 24 and 48 hours. As a result, it was obtained that the best carbon source was refined sugar and brown sugar, which show better results in the growth of microorganisms, since the cost of the other materials considerably exceeds the value accessible to students. The ANOVA resulted with a p-value less than 0.05, which means that there are no statistically significant differences between the treatments and the control that was the commercial culture medium. It was possible to develop a culture medium for bacteria, with homemade materials, proving to be viable and inexpensive.
Keywords: Bacillus subtilis; COVID; culture medium; viability; bacteria